PORTRAYING HEDONISM IN CRAZY RICH ASIAN NOVEL BY KEVIN KWAN - Susanto, Joni (TELL - US JOURNAL, 2022)
Modern society has the view that hedonism is a lifestyle that only emphasizes pleasure such as shopping for luxury goods and eating expensive food. This is contrary to the simple lifestyle proposed by Epicureans. Epicureans distinguish between natural desires that are needed (such as eating) and natural desires that are allowed (such as delicious food), and vain desires (such as wealth) (K. Bertens, 2000). Therefore, hedonism does not always have to prioritize luxury but can improve the quality of enjoyment itself. Evolving the issue of flexing in society is often done by the youth as a negative stigma yet it could be positive if it is seen from a different angle. This study also identifies the influence of hedonism on the main character's life. In this research, the researcher used the qualitative method to analyze the data as it is concerned with the subjective assessment of attitudes, opinions, and behavior. The finding of this research was that natural desires are allowed to have the effect of being able to (1) enjoy life more, (2) have a high social spirit, and (3) be wise in dealing with problems. The impact of vain desires tends to be (1) anti-social, (2) excessive consumptive behavior, and (3) unsatisfactory